PENYULUHAN DAN SOSIALISASI SISTEM LAYANAN ”PORTAL EMAS” PADA MAHASISWA UNIVERSITAS PANCA MARGA - Supriyanto; Nurul Jannah Lailatul Fitria (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Innovations in public sector services continue to vary and become more sophisticated. The government always tries to innovate in public sector services. As implemented by the Probolinggo City Government with the Portal Emas application. Online services through applications that include oral, written, and even direct action services. However, there are still many people who have not used the Portal Emas application. So that the community service team from 2019 students of the Public Administration Study Program, Faculty of Social and Political Sciences, Panca Marga University compiled a community service program with the theme of Extension and Socialization of the Probolinggo City